ARTIFICIAL INTELLIGENCE-APPLICATION IN THE FIELD OF E-COMMERCE - p, Gururaj (International Journal of Research -GRANTHAALAYAH, 2021)
Artificial intelligence is playing a vigorous role in the present era. This concept is not a new concept but development in the area of artificial intelligence is continuously happing since the initiation of the concept. Development of the intelligent systems is making the human work easier and also convenient and save most of the time and effort. This paper simply describes the current state of e-commerce development and AI technology prospects, analyses the current state of AI technology application in the field of e-commerce, and focuses on studying and discussing in detail from the perspectives of Artificial Intelligence Assistant (chatbot), intelligent logistics, Recommendation Engine, Warehouse Automation, Visual Search and optimal pricing application through the research of e-commerce intelligent operation.